2016
DOI: 10.1364/oe.24.00a388
|View full text |Cite
|
Sign up to set email alerts
|

Directional sideward emission from luminescent plasmonic nanostructures

Abstract: Periodic arrays of metallic nanoparticles can be used to enhance the emission of light in certain directions. We fabricated hexagonal arrays of aluminium nanoparticles combined with thin layers of luminescent material and optimized period (275 nm) and thickness (1500 nm) to obtain sideward directional emission into glass for a wavelength band around 620 nm. The key physics is that the luminescent layer acts as a waveguide, from which light is emitted at preferential angles using diffractive effects. This pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…To compare these experimental findings with theory, we performed numerical simulations of the emission patterns. The chosen approach is based on the reciprocity principle, , allowing us to take into account the periodicity of the structure, the substrate, and the spatial distribution of the emitters. We assumed that the emission of the glass substrate can be represented by point-like electric dipole emitters, which are randomly oriented and homogeneously distributed within the glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…To compare these experimental findings with theory, we performed numerical simulations of the emission patterns. The chosen approach is based on the reciprocity principle, , allowing us to take into account the periodicity of the structure, the substrate, and the spatial distribution of the emitters. We assumed that the emission of the glass substrate can be represented by point-like electric dipole emitters, which are randomly oriented and homogeneously distributed within the glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] Periodic arrays of metallic nanoparticles on transparent substrates and their complementary structures, i.e., periodic nanohole arrays etched in metallic layers, have been widely studied for their unique optical properties. 9 These properties include the existence of spectrally sharp collective optical resonances, [10][11][12][13][14][15][16][17] the ability to control spontaneous emission, [18][19][20][21] the ability to disperse 22 and focus light, 23,24 the ability to support lasing, 25,26 and the extraordinary transmission of light through nanohole arrays. 27,28 Numerous applications of nanoparticles and nanohole arrays as chemical and biological sensors have been described in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…In several of the most recent publications cited above, 18,20,21,25,26,[42][43][44] k-space optical microscopy is key in the elucidation of the investigated physical mechanisms. Recently, it has also been reported that k-space optical microscopy may be used to take advantage of a previously disregarded artifact from microscope objectives, called the "condenser effect," in order to resolve the geometry of periodic nanoparticle arrays beyond the optical diffraction limit.…”
Section: Introductionmentioning
confidence: 99%
“…The natures of the resonant modes were rigorously analyzed with the multipole decomposition theory, which was exploited to examine the selective coupling between the emitter and the nanoantenna. The far field radiation pattern was carefully studied not only for a single fluorescence emitter to explore the physical insight but also for an assembly of random-oriented incoherent emitters via the reciprocity principle to better mimic realistic situations. The resultant excitation rate, quantum yield, radiative/nonradiative decay rate, fluorescence enhancement factor, and collection efficiency were thoroughly investigated to evaluate the performance of the hybrid mushroom nanoantenna.…”
Section: Introductionmentioning
confidence: 99%